2005
DOI: 10.1542/peds.2004-0815f
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Patterns and Sleep Problems Among Schoolchildren in the United States and China

Abstract: As reported by parents, children in China went to bed later and woke up earlier and their sleep duration was 1 hour shorter than the US children. Chinese children were reported to have more sleep problems than their US counterparts. Daytime sleepiness was determined by sleep duration only for those who slept insufficiently. Unique school schedules and sleep practices may contribute to the differences in the sleep patterns and sleep problems of children from the United States and China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
320
16
21

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(390 citation statements)
references
References 31 publications
28
320
16
21
Order By: Relevance
“…Primary school children in China averaged 9.3 vs 10.2 hours of sleep compared with US children and reported daytime sleepiness. 40 Cross-sectional analysis of child journals and caregiver questionnaires for 755 children aged 8 to 11 years showed that at all ages minority boys slept significantly less compared with minority girls and all nonminority children. 8 A parent-report survey of 472 children in 1 US city showed an inverse association between socioeconomic status and both parasomnias and noisy sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Primary school children in China averaged 9.3 vs 10.2 hours of sleep compared with US children and reported daytime sleepiness. 40 Cross-sectional analysis of child journals and caregiver questionnaires for 755 children aged 8 to 11 years showed that at all ages minority boys slept significantly less compared with minority girls and all nonminority children. 8 A parent-report survey of 472 children in 1 US city showed an inverse association between socioeconomic status and both parasomnias and noisy sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to adults, this morning routine is usually less internalized and self-governed. Second, night-time sleep duration decreases and morning drowsiness increases across childhood and adolescence (Carskadon, 1990;Sadeh et al, 2000;Fallone et al, 2002;Liu et al, 2005). Fewer changes in sleep habits are observed among adults.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to socio-demographic factors, children of Caucasian ethnicity have been indicated to sleep longer than children of other ethnicities. [6][7][8][9] Age is inversely associated with sleep deprivation. 10 The role of environmental factors on sleep duration is unclear, but there are indications that the physical and socio-cultural home environment play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to socio-demographic factors, children of Caucasian ethnicity have been indicated to sleep longer than children of other ethnicities. [6][7][8][9] Age is inversely associated with sleep deprivation. 10…”
mentioning
confidence: 99%